Arnaus. Um pintor a fresco no Norte de Portugal na 1.ª metade do século XVI - Rosas, Lúcia (2008)
The quality and novelty of painter Arnaus's work in churches and chapels around the areas of Entre-Douro-e-Minho and Trás-os-Montes is a large and central research field. Crucially, it reveals a sound territorial organization, the connection between patrons and works of art, and the relationship between monasteries and parish churches, from the end of the middle-ages until the beginning of modern times.